1999
DOI: 10.1128/mcb.19.12.8272
|View full text |Cite
|
Sign up to set email alerts
|

Paired-Homeodomain Transcription Factor PAX4 Acts as a Transcriptional Repressor in Early Pancreatic Development

Abstract: The paired-homeodomain transcription factor PAX4 is expressed in the developing pancreas and along with PAX6 is required for normal development of the endocrine cells. In the absence of PAX4, the numbers of insulin-producing beta cells and somatostatin-producing delta cells are drastically reduced, while the numbers of glucagon-producing alpha cells are increased. To gain insight into PAX4 function, we cloned a full-length Pax4 cDNA from a beta-cell cDNA library and identified a bipartite consensus DNA binding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
185
1
6

Year Published

2000
2000
2015
2015

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 171 publications
(203 citation statements)
references
References 46 publications
11
185
1
6
Order By: Relevance
“…Reporter Gene Constructs and Expression Plasmids-To generate reporter plasmids, fragments of the 5Ј region of NEUROG3 obtained by restriction digestion or PCR using the pFOX Luc1 NEUROG3-5.7kb plasmid (13) as a template were ligated upstream of the luciferase gene in pFOX Luc1 plasmids or upstream of the thymidine kinase (TK) minimal promoter in pFOX Luc1TK plasmids (14). Mutagenesis of the reporter gene constructs was performed using a Quick Change sitedirected mutagenesis kit according to the manufacturer's instructions (Stratagene, La Jolla, CA).…”
Section: Methodsmentioning
confidence: 99%
“…Reporter Gene Constructs and Expression Plasmids-To generate reporter plasmids, fragments of the 5Ј region of NEUROG3 obtained by restriction digestion or PCR using the pFOX Luc1 NEUROG3-5.7kb plasmid (13) as a template were ligated upstream of the luciferase gene in pFOX Luc1 plasmids or upstream of the thymidine kinase (TK) minimal promoter in pFOX Luc1TK plasmids (14). Mutagenesis of the reporter gene constructs was performed using a Quick Change sitedirected mutagenesis kit according to the manufacturer's instructions (Stratagene, La Jolla, CA).…”
Section: Methodsmentioning
confidence: 99%
“…Construction of pBAT12.mPAX4, the DNA plasmid expressing mouse PAX4 under the control of the human cytomegalovirus (CMV) immediate-early gene promoter, has been described previously (16). Mutations in the paired domain (S43P and R44P) and the homeodomain (N220P and R222P) in the mouse PAX4 cDNA were produced in the pBAT12.mPAX4 plasmid and confirmed by sequencing.…”
Section: ј-Rapid Amplification Of Cdna Ends (Race)-mentioning
confidence: 99%
“…One of these islet cell-type determination factors is the paired homeodomain transcription factor PAX4. PAX4 functions as a potent transcriptional repressor and is expressed only transiently in the fetal pancreas, peaking during the period of beta and delta cell differentiation (16). Mice with a targeted disruption of the pax4 gene have a marked decrease in beta and delta cells with a commensurate increase in alpha cells (17), suggesting that PAX4 functions by repressing the alpha cell differentiation program and thereby deviates cells from a default alpha cell fate to an alternate beta or delta cell fate.…”
mentioning
confidence: 99%
“…54 Pax4 is expressed at e9.5 in the dorsal and ventral buds but is limited to the first and second wave b-cells; however, it is down-regulated shortly after birth and undetectable in adult islets. [184][185][186] Additionally, lineage tracing revealed that Pax4 C cells represent specified endocrine progenitors that may commit to endocrine cell fate. 187,188 Pax4 is expressed downstream of Ngn3 and its expression is lost in Ngn3 ¡/¡ mice but not vice versa.…”
Section: Islet 1 (Isl1)mentioning
confidence: 99%
“…186 Also, Pax4 is a repressor of both ghrelin expression and Pax6-mediated glucagon expression; hence there is elevated expression of these 2 cell types in Pax4 mutants. 185,188,189 A loss in Pax4 expression inhibits Pdx1, Hb9 and insulin mRNA in b-cell precursors. 190 Ectopic expression of Pax4 and Arx prompts the formation of b-and a-cell lineage respectively.…”
Section: Islet 1 (Isl1)mentioning
confidence: 99%